2008
DOI: 10.3189/002214308784409116
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the forces that drive ice-shelf rift propagation on the Amery Ice Shelf, East Antarctica

Abstract: During these campaigns we detected seven bursts of episodic rift propagation. To determine whether these rift propagation events were triggered by short-term environmental forcings, we analyzed simultaneous ancillary data such as wind speeds, tidal amplitudes and sea-ice fraction (a proxy variable for ocean swell). We find that none of these environmental forcings, separately or together, correlated with rift propagation. This apparent insensitivity of ice-shelf rift propagation to short-term environmental for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 27 publications
3
100
1
Order By: Relevance
“…Several authors have suggested that calving from ice shelves and ice tongues may be triggered by flexural stresses induced by ocean swell (Holdsworth & Glynn 1978;MacAyeal et al 2006;Sergienko 2010), despite some contradictory observations that ice shelf rift propagation itself is not influenced by ocean swell (Bassis et al 2007(Bassis et al , 2008. To examine the role of ocean swell in generating transient stresses that contribute to failure of floating ice tongues, we estimated the magnitude of the horizontal stress induced in the ice following the order of magnitude estimation procedure described by Bassis et al (2007Bassis et al ( , 2008.…”
Section: (D) the Role Of Ocean Swell In Triggering Calving Events Fromentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have suggested that calving from ice shelves and ice tongues may be triggered by flexural stresses induced by ocean swell (Holdsworth & Glynn 1978;MacAyeal et al 2006;Sergienko 2010), despite some contradictory observations that ice shelf rift propagation itself is not influenced by ocean swell (Bassis et al 2007(Bassis et al , 2008. To examine the role of ocean swell in generating transient stresses that contribute to failure of floating ice tongues, we estimated the magnitude of the horizontal stress induced in the ice following the order of magnitude estimation procedure described by Bassis et al (2007Bassis et al ( , 2008.…”
Section: (D) the Role Of Ocean Swell In Triggering Calving Events Fromentioning
confidence: 99%
“…To examine the role of ocean swell in generating transient stresses that contribute to failure of floating ice tongues, we estimated the magnitude of the horizontal stress induced in the ice following the order of magnitude estimation procedure described by Bassis et al (2007Bassis et al ( , 2008. The stress due to ocean swell is taken as the maximum stress imparted to the ice, assuming wavelengths for ocean swell that range from 100 to 750 m (all within the most energetic portion of the ocean swell spectrum) and assuming an amplitude of 2 m (comparable to significant wave heights).…”
Section: (D) the Role Of Ocean Swell In Triggering Calving Events Fromentioning
confidence: 99%
“…For example, calving via the detachment of large, tabular icebergs is an important end-member of observed calving styles (Amundson and Truffer, 2010). The fractures that determine the size of very large icebergs -such as the "loose tooth" at the terminus of the Amery Ice Shelf, and thus the calving rate in these locations -are exactly those features that result from ductile and brittle deformation over yearly to decadal timescales (Bassis et al, 2008). Thus while the elastic component of stress relaxes away over long-term simulations, the fractures resulting from the elastic component of stress remain and affect the ice dynamics (e.g., the complete disintegration of the Larsen B Ice Shelf, examined by Glasser and Scambos, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In nature, calving results from the fracture of ice and is a consequence of ductile and brittle deformation (van der Veen, 1998;Weiss, 2004). Ductile fracture is initiated by the formation of micro-cracks that eventually coalesce to form a macroscopic fracture (seen for example in the Amery Ice Shelf; Bassis et al, 2008) and is a slow process for which weakening by micro-cracks occurs over a prolonged stress plateau. On the other hand, the breaking or damage process for brittle fractures occurs abruptly for a given value of stress and strain rate (Sammonds et al, 1998;Schulson and Duval, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the ice calving represents a sudden change in the value of the outgoing ice flux (ubH ) due to a sudden change in the ice thickness (H ) at the terminus. Considering the complex environmental impact on ice shelves (Bassis et al, 2008), from the mathematical perspective it can be suggested that at long timescales the calving processes are described by a stochastic model, which considers the size of the anticipated ice debris as a random value. This value satisfies a probability distribution law, similar to the Gaussian distribution for example.…”
Section: Prognostic Experimentsmentioning
confidence: 99%